Major legal systems of the world - Ali Mohamed, Ashgar Ali; Ahmad, Muhamad Hassan (CLJ Publication, 2020)
In some countries such as Malaysia, the legal system is composed of the common law system and the Islamic law system. The application of the common law system in Malaysia was a direct result of the British administration of the Malay Peninsular and the Borneo states for more than 150 years which had left greater impact upon the law of the country. Further, art. 121(1A) of the Federal Constitution also provides for a dual justice system in Malaysia. Having said the above, this chapter discusses the major legal systems across the world, i.e., civil law system, common law system, and Islamic legal system in conjunction with the emergence of mixed legal systems